Using Performance (with Audience Participation) to Help Translators Discern Ambiguity in Texts: An Empirical Study Based on the Book of Ruth. Issue 2 (August 2020) - Dickie, June F.
Written text often has ambiguities or "gaps, " requiring readers to bring their own experience into making sense of the story (in line with reception theory). Translators need to be able to identify such gaps, determine if they are intentional or not, and then decide how best to deal with them in translation. In this study, oral performance of a text is used, with audience participation, to discern ambiguities and gaps. Two groups in South Africa present a performance of the book of Ruth to three audiences. A jester questions the audience, at particular points in the story, as to their perceptions of characters' moods or motivations. The book of Ruth, being largely dialogue, lends itself to dramatic performance, but the methodology could be applied to any text, with enlightening results. The approach shows that by imagining texts as performances, translators can become more aware of ambiguities and decide how they should be treated.